Risk Assessment of Blockchain Technology - Morganti, Giacomo; Schiavone, Enrico; Bondavalli, Andrea (Anais do Latin-American Symposium on Dependable Computing (LADC), 2018)
Recently, blockchain has attracted a great interest, and today it is considered not only as an innovative technology, but as a potential revolution for the world of business. The motivation of this enthusiasm is due to its capability of enabling new forms of records-keeping, transactions, and interactions between decentralized and mistrusting entities. Indeed, blockchain is driving companies to huge investments and strategic acquisitions, and it is raising innovation and research across industries and academia. However, besides the opportunities offered, this technology may expose institutions and interacting parties to new risks that have to be discovered, understood, and, where possible, eliminated or at least reduced. In this paper we identify the main threats of blockchain and assess their related impact. Then, applying a NIST-compliant approach, we perform a qualitative risk assessment. Finally, we review the possible countermeasures, where existing, for each threat analyzed, and discuss open challenges and future directions.